2020
DOI: 10.21873/cgp.20198
|View full text |Cite
|
Sign up to set email alerts
|

Chromobox 2 Expression Predicts Prognosis After Curative Resection of Oesophageal Squamous Cell Carcinoma

Abstract: Background/Aim: To investigate the function of chromobox 2 (CBX2) in oesophageal squamous cell carcinoma (OSCC). Materials and Methods: We used real-time quantitative reverse transcription PCR (qRT-PCR) and immunohistochemistry to determine CBX2 expression levels in 13 human OSCC cell lines and clinical specimens of two independent cohorts of patients with OSCC. Results: PCR array analysis revealed that CBX2 was co-ordinately expressed with WNT5B in OSCC cell lines. RT-qPCR analysis of clinical samples reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Oral squamous cell carcinoma (OSCC) is one of the most frequent malignant tumors with a poor prognosis ( 1 , 2 ), and the incidence of OSCC is ~300,000 new cases per year worldwide ( 3 ). Recent reports revealed that betel quid chewing, smoking and human papillomavirus infections are the three biggest risk factors that contribute to the tumorigenesis of OSCC ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is one of the most frequent malignant tumors with a poor prognosis ( 1 , 2 ), and the incidence of OSCC is ~300,000 new cases per year worldwide ( 3 ). Recent reports revealed that betel quid chewing, smoking and human papillomavirus infections are the three biggest risk factors that contribute to the tumorigenesis of OSCC ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 21 ESCC cell lines, specifically KYSE30, KYSE70, KYSE140, KYSE150, KYSE180, KYSE270, KYSE410, KYSE450, KYSE510, KYSE590, KYSE890, KYSE1170, KYSE1260, KYSE1440, NUEC2, TE1, TE2, TE3, WSSC, TT, and TTn, along with Het‐1A, a non‐cancerous epithelial cell line, were purchased from the Japanese Collection of Research Bioresources Cell Bank (Osaka, Japan), the American Type Culture Collection (Manassas, VA, USA), or were established at Nagoya University 5 . The cells were cultured in a humidified incubator at 37°C with an atmosphere composition of 5% CO 2 using RPMI‐1640 (Sigma‐Aldrich, St. Louis, MO, USA) supplemented with 10% fetal bovine serum and antibiotics 24 …”
Section: Methodsmentioning
confidence: 99%
“…Expression of CBXs in cancers. Compared with normal tissues or paracancerous tissues, the expression of all or some of the CBX1/2/3/4/5/8 members is upregulated in most cancer tissues, including glioma (67-69), tongue squamous cell carcinoma (TSCC) (70), head and neck squamous cell carcinoma (HNSCC) (71), breast cancer (BC) (15,(72)(73)(74)(75)(76)(77)(78)(79)(80), non-small cell lung cancer (NSCLC) (81)(82)(83)(84)(85), esophageal cancer (EC) (86)(87)(88)(89)(90), gastric cancer (GC) (91)(92)(93)(94)(95)(96)(97)(98), pancreatic adenocarcinoma (PAAD) (99,100), colorectal cancer (CRC) (101-104), urinary bladder cancer (UBC) (105), sarcoma (106) and osteosarcoma (107,108). As a tumor suppressor, CBX7 is expressed at low levels in most tumors, such as glioma, HNSCC (71), EC (87,88), GC (93)(94)(95)(96)(97)(98), PAAD (109), CRC (103,104), clear cell r...…”
Section: Expression Of Cbxs In Cancers and The Relationship Between C...mentioning
confidence: 99%
“…invasion↑ osteosarcoma ( 107) was reported to be associated with more robust metastatic characteristics, indicating that CBX3 has an important role in tumor metastasis. High expression of CBX2/3/8 in glioma (67,69), CBX2 in EC (89) and CBX1 in HCC (115) was indicated to lead to a high probability of tumor recurrence. In terms of other cancer characteristics, CBX2/6/7 is closely related to the isocitrate dehydrogenase mutation in glioma (68), CBX2 is related to a human epidermal growth factor receptor (EGFR)2-positive status of BC ( 74) and CBX3 is related to EGFR mutation in NSCLC (82).…”
Section: Othersmentioning
confidence: 99%